2023
DOI: 10.1039/d2qi02554j
|View full text |Cite
|
Sign up to set email alerts
|

A ratiometric fluorescent probe based on a dual-ligand lanthanide metal–organic framework (MOF) for sensitive detection of aluminium and fluoride ions in river and tap water

Abstract: In this work, we report a ratiometric fluorescence probe towards Al3+ and F- using lanthanide Metal−Organic Framework material, Eu-BDC-NH2/TDA, which is composed of a metal centre Eu3+, BDC-NH2 and TDA...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…Due to the energy mismatch between the ligand and Al 3+ , the increase of π* → π energy transfer of the ligand led to the enhanced fluorescence. 47–49 Several previous studies also reported similar phenomena and results. 50,51…”
Section: Resultssupporting
confidence: 68%
“…Due to the energy mismatch between the ligand and Al 3+ , the increase of π* → π energy transfer of the ligand led to the enhanced fluorescence. 47–49 Several previous studies also reported similar phenomena and results. 50,51…”
Section: Resultssupporting
confidence: 68%
“…Our previous work also supports this viewpoint. 23 The energy gap (ΔE) between Eu 3+ and triplet-state energy (T1) of BDC-NH 2 is lower than 2500 cm −1 , which is the minimum energy range for effective sensitisation. 35,36 Whereas, the ΔE between Eu 3+ and T1 of TDA matches the optimal energy level required for ligand-to-metal charge transfer (LMCT) process.…”
Section: Characterisation Of Eu-mofmentioning
confidence: 95%
“…To prepare ratiometric fluorescent sensors, the constructed materials need to produce double/multiple emission peaks. Lanthanide-based metal–organic frameworks (Ln–MOFs) have been used broadly in the preparation of ratiometric fluorescent sensing materials, which have been applied to the detection of ions, temperature, pH, biomolecules, etc. Ln–MOFs can be used to prepare ratiometric sensors primarily depending on their modulated “antenna effect”. The degree of energy transfer between ligand and Ln 3+ directly affects whether the emission peaks of ligand and Ln 3+ ions can appear simultaneously. Therefore, the selection of appropriate ligands is the key to constructing Ln–MOFs with dual-emission peaks. According to Latva’s rule, the Eu 3+ ion can be effectively sensitized when the energy gap between the 5 D 0 state of the Eu 3+ ion and the triplet state (T 1 ) of the ligand is in the range of 2500–4000 cm –1 .…”
Section: Introductionmentioning
confidence: 99%